Students' Moral Development through the Study of Akhlak Lil Banin - Regi Laila Astuti; Agus Fakhruddin; Ganjar Eka Subakti (Journal of Science and Education (JSE), 2024)
This research aims to identify the process of fostering student morals and analyze its impact and factors in shaping student character. This research uses a descriptive qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and documentation with teachers and students related to the implementation of the study of Akhlak Lil Banin and secondary data through journals, e-books, and others that support the research. This research analyzes data through steps that include, such as data collection, data reduction, data presentation, conclusion drawing and verification to ensure the validity of the findings. To validate the data, this research uses triangulation techniques. The results show that the method of moral development through advice, exemplary, habituation, and targhib and tarhib has a positive impact in shaping manners, respect for parents and teachers, and increasing the discipline of worship. School, family, and community environmental factors play a role in the success of this coaching, with student interest and motivation being internal factors that support it. Thus, moral development through the study of Akhlak Lil Banin effectively shapes student character and is relevant to be applied in education to form a generation with noble character